Economia da educação: Gestão e fenômeno de mercado - Popov, Rinad A.; Prokhorova, Victoria V.; Zakharova, Elena N.; Ordynskaya, Marina E.; Gabidullina, Chulpan F. (Revista on line de Política e Gestão Educacional, 2022)
Education economics is regarded as the study of education-related economic issues, such as the need for education, the financing and requirement of education, and the comparative effectiveness of several educational programs and procedures. The main aim of the study is to analyze administration and market phenomenon in the arena of education economics. To fulfil that aim, the methodological basis for the analysis of the problems concerning the functioning and purposeful development of spatially localized socio-economic systems is formed by the works of economic theory classics, the theory of organizations, the work of modern scientists in the field of education economics. The solution to this problem seems to be possible through the multi-level implementation of BIM technologies in economic administration within the Russian territorial and economic practice, built on the principles of network modeling of the reproduction process.